2003
DOI: 10.1136/gut.52.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the oncogene c-myc in Barrett's adenocarcinoma: induction of c-myc by acidified bile acid in vitro

Abstract: Background and aims: C-myc over expression is implicated in malignancy although to date this has not been studied in Barrett's metaplasia. We sought to determine c-myc expression in the malignant progression of Barrett's metaplasia and whether it may be induced by bile acids seen in gastro-oesophageal refluxate. Methods: C-myc protein and mRNA levels were assessed in 20 Barrett's metaplasia and 20 oesophageal adenocarcinoma samples by western blotting and real time polymerase chain reaction. Levels of c-myc an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 26 publications
8
110
0
Order By: Relevance
“…Bile acids, particularly unconjugated bile acids such as DCA, are a component of gastro-duodenal reflux that have been strongly linked to BE development. [26][27][28] In previous studies, DCA showed the strongest effect on Cdx2 transcription of all bile acids. [29][30][31] In our earlier reports, we proposed that bile acids suppress the expression of Hes1 via Cdx2 activation in esophageal epithelial cells, with resulting activation of ATOH1 and MUC2.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids, particularly unconjugated bile acids such as DCA, are a component of gastro-duodenal reflux that have been strongly linked to BE development. [26][27][28] In previous studies, DCA showed the strongest effect on Cdx2 transcription of all bile acids. [29][30][31] In our earlier reports, we proposed that bile acids suppress the expression of Hes1 via Cdx2 activation in esophageal epithelial cells, with resulting activation of ATOH1 and MUC2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, myc overexpressing mice demonstrate increased incidence of tumours (Pelengaris et al, 1999). The expression of c-MYC in human oesophageal malignancy has previously been documented, demonstrating that c-MYC expression is elevated in Barrett's metaplasia and further overexpressed in oesophageal adenocarcinoma (Tselepis et al, 2003;Schmidt et al, 2007). The gene encoding c-MYC is located within chromosomal region 8q23 -24.2, a region frequently amplified in adenocarcinomas of the oesophagus and gastro-oesophageal junction and that has been detected in Barrett's metaplasia (Walch et al, 2000;Croft et al, 2002;Doak et al, 2003;van Dekken et al, 2006).…”
mentioning
confidence: 99%
“…Bile acids have been shown to be damaging to esophageal epithelial cells by affecting membrane permeability, cell proliferation and differentiation, increasing free radicals, inducing DNA damage and up-regulating oncogenes [11,[14][15][16][17][18][19][20]. More specifically, both gastric acid and bile acids have been shown to activate NF-kappa B, a major molecule that is up-regulated in and intrinsic to cancer development.…”
Section: Hpimentioning
confidence: 99%